2017
DOI: 10.1111/agec.12359
|View full text |Cite
|
Sign up to set email alerts
|

Decent rural employment and farm production efficiency: empirical evidence from Tanzania and Ethiopia

Abstract: Promoting decent rural employment, by creating new jobs in rural areas and upgrading the existing ones, could be one of the most efficient pathways to reduce rural poverty. This article systematically investigates the impact of decent rural employment on agricultural production efficiency in Ethiopia and Tanzania. The analysis applies an output-oriented distance function approach with an estimation procedure that accounts for different technological, demographic, socioeconomic, institutional, and decent rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 66 publications
1
18
0
1
Order By: Relevance
“…Any positive effect on labor demand may thus not translate into higher wages for laborers and rural youth, but rather only into a higher number of employment opportunities. Yet, more decent working conditions are also an important pathway toward rural poverty reduction and livelihoods development (Ayenew et al., ). These agricultural wage labor opportunities may thus not provide sustainable avenues out of poverty for the future of youth .…”
Section: Resultsmentioning
confidence: 99%
“…Any positive effect on labor demand may thus not translate into higher wages for laborers and rural youth, but rather only into a higher number of employment opportunities. Yet, more decent working conditions are also an important pathway toward rural poverty reduction and livelihoods development (Ayenew et al., ). These agricultural wage labor opportunities may thus not provide sustainable avenues out of poverty for the future of youth .…”
Section: Resultsmentioning
confidence: 99%
“…Limited literature has used SFA in livestock production efficiency measurements in Africa (e.g., Ayenew et al, ; Kavoi, Hoag, & Pritchett, ; Kibiego, Lagat, & Bebe, ; Manyeki & Kotosz, ; Masunda & Rudo, ; Ogunniyi, ; Otieno, Hubbard, & Ruto, ). The common feature of the models as they appear in the different studies is similar to the model originally developed by Aigner et al (), which assumes that the inefficiency term follows half‐normal distribution.…”
Section: Theoretical and Empirical Modelmentioning
confidence: 99%
“…The alternative translog model is not monotonic or globally convex, like the CD model, and imposing the appropriate curvature on it is generally a challenge. However, some scholars prefer TL because of its flexibility and because it does not require a priori restrictions on the technologies to be estimated (e.g., Alvarez & del Corral, ; Ayenew et al, ; Otieno et al, ). To avoid the problem of model specification, we considered the two functional forms and assumed that the deterministic part f ( X i ; β ) takes the log‐linear, expressed as: CobbDouglas:lnYi=βo+i=1NβilnXi+viui, Translog:lnYi=βo+i=1NβilnXi+12i=1Nk=1NβiklnXiklnXik+viui, where Y i is the output of producer i , X i is a vector of inputs used by producer i and X i ~ IIDN ( μ , Σ x ) and β i is a vector of the technology parameters to be estimated.…”
Section: Theoretical and Empirical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a study by Ayenew et al. () showed that literate smallholder farmers are more likely to be technically efficient in agriculture than their illiterate counterparts. Sherlund et al.…”
Section: Discussionmentioning
confidence: 99%